Politics of Visibility Young Muslims in European Public Spaces - Jonker, Gerdien; Amiraux, Valérie (Globaler lokaler Islam, 2006)
This book takes into view a large variety of Muslim actors who, in recent years, made their entry into the European public sphere. Without excluding the phenomenon of terrorists, it maps the whole field of Muslim visibility. The nine contributions present unpublished ethnographic materials that have been collected between 2003 and 2005. They track down the available space that is open to Muslims in EU member states claiming a visibility of their own. The volume collects male and female, secular and religious, radical and pietistic voices of sometimes very young people. They all speak about »being a Muslim in Europe« and the meaning of »real Islam«.